ENTREPRENEURSHIP COUNSELING FOR BADUY IN IKAT WEAVING BUSINESS ENHANCES COMPETITIVE ADVANTAGE - Hari Muharram; Andi Hasryningsih Asfar; Icin Quraysin; Ika Pratiwi (International Journal of Engagement and Empowerment, 2022)
Development of Baduy Ikat Woven Cloth gives hope big to the artisans weaving with an opening object tour of Baduy, which has been closed for a long time because of the Covid-19 pandemic. However thereby, competition businesses with the same effort require artisans to increase their competence by accepting new knowledge from outside area ethnic groups Baduy like knowledge about entrepreneurship, the importance of branding for the product, financial and marketing strategy including inside it is the promotion for increase power product competitiveness the weaving permanent attracted by incoming consumers to Baduy or special parties come for buy product for sale back. Management effort Baduy woven cloth still needs to be conducted professionally for face power increasingly competitive moment this. Form Devotion is Counseling Entrepreneurship by giving knowledge directly to the place craftsman tenin baduy with the hope that they could touch now to the people, especially the perpetrators, effortlessly